ANALYSIS OF STUDENT SCIENTIFIC PROCESS SKILL BY APPLYING OF INQUIRY TRAINING LEARNING MODEL AND STUDENT CRITICAL THINKING ABILITY - Rikardo Marpaung; Derlina Nst (Jurnal Pendidikan Fisika, 2018)
The research aims to find out whether the science process skills of students who are taught with inquiry training model better than direct instruction learning, to know whether the science process skills of students who have the ability to think critically above the average is better than students who have the ability to think critically below average, to find out whether there is an interaction between the learning model between the learning model and the critical thinking ability in improving the students' science process skills. This research is a quasi experimental research with two group pretest-posttest design design. The study population is all students of class XI SMA Negeri 1 Pintupohan semester II academic year 2016/2017. Sample in this research is taken by cluster random class, that is as much as 2 class which amount 60 people. Class X-1 as an experimental class taught with inquiry training model consists of 30 students, while X-2 class as control class is taught by direct instruction learning consist of 30 students. The instrument of this research consists of two types of science process skill instruments consisting of 10 questions in the form of test essay, and students' critical thinking ability instrument consists of 5 questions in the form of test essay. The resulting data, analyzed by using two path Anava and H0 accepted means there is no interaction between instructional model inquiry training and direct instruction learning with students 'critical thinking skills to improve students' science process skills.